Synthesis of a Conjugated D-A Polymer with Bi(disilanobithiophene) as a New Donor Component - Makoto Nakashima; Yousuke Ooyama; Takuya Sugiyama; Hiroyoshi Naito; Joji Ohshita (Molecules, 2016)
A new conjugated donor-acceptor (D-A) polymer pDSBT2-BT containing bi(disilano-bisthiophene) and benzothiadiazole as donor and acceptor units, respectively, was prepared. The polymer showed a broad UV-vis absorption band at λmax = 599 nm in chlorobenzene. The absorption band was shifted to λmax = 629 nm when the polymer was measured as a film, indicating enhanced interchain interactions of the polymer. Bulk hetero-junction polymer solar cells (BHJ-PSCs) were fabricated using pDSBT2-BT and PC71BM as host and guest materials, respectively. Optimization of cell fabrication conditions provided a maximal power conversion efficiency of 3.3% and the following cell parameters: Voc = 0.86 V, Jsc = 7.56 mA/cm2, and FF = 0.51. Although the efficiency still leaves much to be desired, these data underscore the potential of pDSBT2-BT as a high-voltage polymer solar cell material.